2013
DOI: 10.1038/srep02845
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SHP-2 activity in CD4+ T cells promotes melanoma progression and metastasis

Abstract: The Src homology 2 domain-containing tyrosine phosphatase 2 (SHP-2) has been reported to have both tumor-promoting and tumor-suppressing roles in tumorigenesis. However, the role of SHP-2 in tumor immunity remains unclear. Here we observed progressively lower levels of phosphorylated SHP-2 in tumor-associated CD4+ T cells during melanoma development in a murine model. Similarly, the levels of phosphorylated SHP-2 in the CD4+ T cells of human melanoma specimens revealed a decrease paralleling cancer development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…In addition, immunogenic cancers developed in these mice with kinetics similar to the ones observed in the control groups (156). Along these lines, studies by others showed that the growth of immunogenic tumors in mice lacking Shp-2 in T cells was moderately retarded or accelerated, but even in the former case the effects on tumor growth were distant from the ones of PD-1-deficiency (154,160,161). One interpretation is that the therapeutic effects of PD-1 blockade are not largely mediated by T cells, a quite unlikely hypothesis in light of cytotoxic T cell depletion results (131,162).…”
Section: Shp-2 and Inhibitory Receptor Signaling In T And Nk Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, immunogenic cancers developed in these mice with kinetics similar to the ones observed in the control groups (156). Along these lines, studies by others showed that the growth of immunogenic tumors in mice lacking Shp-2 in T cells was moderately retarded or accelerated, but even in the former case the effects on tumor growth were distant from the ones of PD-1-deficiency (154,160,161). One interpretation is that the therapeutic effects of PD-1 blockade are not largely mediated by T cells, a quite unlikely hypothesis in light of cytotoxic T cell depletion results (131,162).…”
Section: Shp-2 and Inhibitory Receptor Signaling In T And Nk Cellssupporting
confidence: 54%
“…The possibility that SHP-2 inhibits this cascade downstream of PD-1 is difficult to reconcile with its well-documented role in promoting it downstream of growth factor receptors. Moreover, despite the role of SHP-2 in TCR signaling remains controversial (79,(149)(150)(151)(152)(153)(154)(155)(156)(157), a positive effect on ERK engagement has been observed also in this context (149,152,153). The dichotomy in the effects of SHP-2 could be explained by a model in which IRs reduce the availability of the phosphatase, thus preventing its contribution to the ERK cascade, or by a very distinct regulation of SHP-2 activity downstream of IRs and growth factor receptors.…”
Section: Shp-2 and Inhibitory Receptor Signaling In T And Nk Cellsmentioning
confidence: 99%
“…Whether the gene silencing of SHP-1/2 and SOCS-1 favors the progression from MGUS to MM remains to be determined. Finally, our work further emphasizes the implication of SHP-1 , SHP-2 and SOCS-1 genes as suppressors of tumor growth in different cancers [37, 50–52]. …”
Section: Discussionmentioning
confidence: 63%
“…At the basal level, there was no significant difference in the counts of CD4 + and CD8 + T cells, neither in the CD4-CD8 ratio in the spleen or the lymph nodes between WT and SHP2 CD4−/− mice [19]. Next, we examined whether SHP2-deficiency in CD4 + T cells impacts the colitis progression using DSS-induced colitis model.…”
Section: Resultsmentioning
confidence: 99%